220k views
23 votes
Simplify the expression(a4−6a2b2+ b4)−(−2a4+5a2b2+ 3b4) and hence, find its value for a = 2and b = −1.

1 Answer

4 votes

Answer:

(a)
3a^4 - 11a^2b^2 -2b^4

(b)
3a^4 - 11a^2b^2 -2b^4= 2

Explanation:

Given


(a^4 - 6a^2b^2+ b^4) - (-2a^4+5a^2b^2+ 3b^4)

Solving (a): Simplify


(a^4 - 6a^2b^2+ b^4) - (-2a^4+5a^2b^2+ 3b^4)

Open brackets


a^4 - 6a^2b^2+ b^4 +2a^4-5a^2b^2- 3b^4

Collect Like Terms


a^4 +2a^4- 6a^2b^2-5a^2b^2+ b^4 - 3b^4

Simplify Like Terms


3a^4 - 11a^2b^2 -2b^4

Solving (b): Simplify when a = 2 and b = -1


3a^4 - 11a^2b^2 -2b^4


3*(2)^4 - 11*(2^2)*(-1)^2 -2*(-1)^4


3 * 16 - 11 * 4 * 1 - 2 * 1


48 - 44 - 2


= 2

Hence:


3a^4 - 11a^2b^2 -2b^4= 2

User JV Lobo
by
5.8k points